1993
DOI: 10.1007/bf01308811
|View full text |Cite
|
Sign up to set email alerts
|

TheS=1/2 Heisenberg antiferromagnet on the triangular lattice: Exact results and spin-wave theory for finite cells

Abstract: We study the ground state properties of the S= 1 2 Heisenberg antiferromagnet (HAF) on the triangular lattice with nearest-neighbour (J) and next-nearest neighbour (αJ) couplings. Classically, this system is known to be ordered in a 120 • Néel type state for values −∞ < α ≤ 1/8 of the ratio α of these couplings and in a collinear state for 1/8 < α < 1. The order parameter M and the helicity χ of the 120 • structure are obtained by numerical diagonalisation of finite periodic systems of up to N = 30 sites and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 30 publications
4
56
0
2
Order By: Relevance
“…As a result a nonchiral and planar system should acquire values close to zero for this triple product. Some studies [54,58] predict that the THM should be chiral in some circumstances (e.g., considering couplings higher than two-body exchange interactions), while the others [18,26,27,29] strongly suggest that the quantum fluctuations always select a planar spin arrangement, so there is no chiral symmetry breaking.…”
Section: B Scalar Chiralitymentioning
confidence: 99%
See 3 more Smart Citations
“…As a result a nonchiral and planar system should acquire values close to zero for this triple product. Some studies [54,58] predict that the THM should be chiral in some circumstances (e.g., considering couplings higher than two-body exchange interactions), while the others [18,26,27,29] strongly suggest that the quantum fluctuations always select a planar spin arrangement, so there is no chiral symmetry breaking.…”
Section: B Scalar Chiralitymentioning
confidence: 99%
“…For several decades, there has been much discussion [18,26,27,29,58] on the possibility of chiral order in the 2D model. A proper chiral order parameter will detect breaking of P and T symmetry of the wave function while the system preserves PT symmetry.…”
Section: Chiralitymentioning
confidence: 99%
See 2 more Smart Citations
“…Chubukov and Jolicoeur [43] and Korshunov [44] have then shown that quantum fluctuations (evaluated in a spin wave approach) could, like thermal ones, lift this degeneracy of the classical ground states and lead to a selection of the collinear state (see Fig. 3.1) [45]. The first study of the exact spectrum of Eq.…”
mentioning
confidence: 99%